2020
DOI: 10.1016/j.infpip.2020.100082
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic review of healthcare-associated Burkholderia cepacia complex outbreaks: presentation, causes and outbreak control

Abstract: Summary Background Over the past decades, the Burkholderia cepacia complex (BCC) has been linked to multiple healthcare-associated outbreaks. No systematic analysis of these outbreaks has been carried out to date. The aim of this study was to conduct a systematic review of reports on nosocomial BCC outbreaks. Methods Published studies from 1971 until 9/12/2019 presenting nosocomial BCC outbreaks were identified using Embase, Pubme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…In addition to our study, two recent studies also reported nosocomial BCC-associated deaths of COVID-19 patients 41 , 42 . However, all three studies are single case reports and could hardly be used to draw inferences about an undetected BCC-associated nosocomial outbreak whose primary sources have been identified to be contaminated medical products/devices (mainly the disinfectant products) 43 . BCC bacteria, a major threat to hospitalized CF patients, are predominantly localized in the phagocytes and mucus in the CF lung 44 and might accelerate the decline in pulmonary function of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our study, two recent studies also reported nosocomial BCC-associated deaths of COVID-19 patients 41 , 42 . However, all three studies are single case reports and could hardly be used to draw inferences about an undetected BCC-associated nosocomial outbreak whose primary sources have been identified to be contaminated medical products/devices (mainly the disinfectant products) 43 . BCC bacteria, a major threat to hospitalized CF patients, are predominantly localized in the phagocytes and mucus in the CF lung 44 and might accelerate the decline in pulmonary function of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…The outbreaks in German hospitals described herein correspond to the existing evidence on similar outbreaks in high-, low-, and middle-income countries. A first systematic review of BCC outbreak reports published between 1971 and 2019 reported that BCC was associated with 111 nosocomial outbreaks worldwide (20 in Europe), with 2390 affected patients and 240 fatalities (28 directly attributed to BCC) [ 22 ]. Most outbreaks occurred either exclusively in ICUs or with the involvement of the ICU, which is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…A recall of involved medical products is one of the most common reported interventions in outbreaks caused by BCC. Notably, in about one-fourth of the reviewed BCC outbreaks, no source of the outbreak could be detected, making it difficult to introduce targeted infection prevention and control measures and other interventions [ 22 ]. Investigations of the patients’ records and the environment were conducted only in 59.5% of the reviewed outbreaks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations